SISTEM INFORMASI ADMINISTRASI PENJUALAN BUKU DENGAN PENGEMBANGAN WATERFALL BERBASIS WEB - Aqil, Muhammad (Kurawal - Jurnal Teknologi, Informasi dan Industri, 2025)
The development of technology and software has brought great changes in various aspects of life, one of which is in the sales transaction process. Nowadays, sales transactions are increasingly being conducted online through E-Commerce platforms, which offer convenience and efficiency in transactions. However, there are still many bookstores that use conventional methods in the sales process, resulting in several obstacles, such as limited market reach, time efficiency, and less than optimal data management. Therefore, this research aims to design a Book Sales Administration Information System with Web-Based Waterfall Development to overcome the problems that are still faced in the manual bookstore sales transaction process. The method used in this research is the waterfall method, which is one of the oldest software development methods and is linear in nature. This method is applied through several stages, namely requirements analysis, system design, implementation, testing, and maintenance. The information system designed utilizes a database for data management and uses PHP and HTML programming languages in its development. The results of this study show that the information system developed can increase efficiency in the book sales process, facilitate recording transactions, and expand market reach. With this system, bookstores can be more competitive in the face of technological developments and increasingly dynamic market needs.